A comparative analysis of movement and physical activity in early childhood teacher education policy in five Nordic countries - Christiansen, Lars Breum; Ekberg, Jan-Eric; Soini, Anne; Larsen, Robert; Kristjánsdóttir, Gudrún; Froberg, Karsten; Sollerhed, Ann-Christin; Sääkslahti, Arja; Fjørtoft, Ingunn; Vilhjálmsson, Rúnar; Olesen, Line Grønholt (Frontiers in Sports and Active Living, 2024)
Introduction The aim of this study is to investigate the integration of movement and physical activity (MoPA) within Early Childhood Teacher Education (ECTE) policies across Denmark, Finland, Iceland, Norway, and Sweden. This knowledge can inform the development of ECTE policies and practices that promote MoPA in Early Childhood Education and Care (ECEC) in Nordic countries and other countries worldwide. Methods In this study, a Nordic cross-national network of researchers collaborated in investigating policy documents at the national and university levels, which govern the education of ECEC teachers. This study was inspired by the Non-affirmative Theory of Education, which provides a framework for understanding the various influences on curricular development in higher education. Based on this, a four-step comparative analytical process of national and university documents across the Nordic countries was conducted. It included keyword search for MoPA related courses and a qualitative description of MoPA in ECTE. Thus, a combination of investigations of policy documents at the national and university level and expert knowledge set a solid foundation for international comparison. Results The comparative analysis of MoPA in ECTE reveals diverse approaches influenced by national and university policies. A central theme is the variability in MoPA integration across these nations. Finland and Norway prioritize MoPA with independent mandatory courses. In Iceland, compulsory MoPA courses exist at one of two universities, and in Sweden at three out of 19. All university colleges in Denmark offer an elective course. Furthermore, learning objectives related to MoPA are, to varying degrees, part of the internships in the countries, with Sweden being an exception. In the participating countries, the teachers decide the content of the MoPA courses with little guidance, support, and agreement on essential MoPA content within and across the ECTE's. Norway has established guidelines, and in Finland, there is a network of ECTE Physical Education (PE) educators, which, to some degree, increases the consistency and quality of MoPA in education. Discussion The Nordic countries present diverse MoPA integration approaches rooted in national policies and educational traditions. The findings emphasize the necessity of independent and mandatory MoPA courses, integration of MoPA into internships and promoting networks across the educational and academic sectors to equip future early childhood educators with competencies for fostering physical activity, motor development and children's well-being.